Real‐world effectiveness and safety of ustekinumab for the treatment of Crohn's disease: the Scottish ustekinumab cohort. Issue 8 (5th March 2021) - Plevris, Nikolas; Fulforth, James; Siakavellas, Spyros; Robertson, Andrew; Hall, Rebecca; Tyler, Amy; Jenkinson, Philip W; Campbell, Iona; Chuah, Cher Shiong; Kane, Claire; Veryan, Jennifer; Lam, Wai Liam; et al.
Abstract: Background and Aim: Ustekinumab is a monoclonal antibody that targets interleukin‐12/23. In Scotland, it was approved for the treatment of moderate to severe Crohn's disease in 2017. The objective of this study was to establish the real‐world effectiveness and safety of ustekinumab in the treatment of Crohn's disease. Methods: We conducted a retrospective study of patients receiving ustekinumab across eight Scottish National Health Service health boards between 2017 and 2019. Inclusion criteria included a diagnosis of Crohn's disease with symptoms attributed to active disease plus objective signs of inflammation at baseline (C‐reactive protein ≥ 5 mg/L or fecal calprotectin ≥ 250 μg/g or inflammation on endoscopy/magnetic resonance imaging) and completion of induction plus at least one clinical follow‐up at 8 weeks. Kaplan–Meier survival analysis was used to establish 12‐month cumulative rates of clinical remission, mucosal healing, deep remission, and perianal fistula response. Rates of serious adverse events were described quantitatively. Results: Our cohort consisted of 216 patients (female sex, 37.9%; median age, 39.0 years, interquartile range [IQR] 28.8–51.8 years; disease duration, 9.9 years, IQR 6.0–16.5 years; prior biologic, 98.6%) with a median follow‐up of 35.0 weeks (IQR 17.4–52.0 weeks). Twelve‐month cumulative rates of clinical remission, mucosal healing, and deep remission (clinical remission plus mucosal healing) were 32.0%, 32.7%, and 19.3%, respectively. In patients with active perianal disease ( n = 37), the 12‐month cumulative perianal response rate was 53.1%. The serious adverse event rate was 13.6 per 100 patient‐years of follow‐up. Conclusion: Ustekinumab is a safe and effective treatment for the treatment of complex Crohn's disease.